Dyslipidemia and eye diseases in the adult Chinese population: the Beijing eye study - Wang, Shuang; Xu, Liang; Jonas, Jost B. (PLOS ONE, 2012)
To determine associations between dyslipidemia and ocular diseases, the population-based Beijing Eye Study 2006 examined 3251 subjects (age≥45 years) who underwent a detailed ophthalmic examination and biochemical blood analysis. Dyslipidemia was defined as any of the following: hypercholesterolemia (total cholesterol concentration≥5.72 mmol/L (220 mg/dL)) or hypertriglyceridemia (triglyceride concentration≥1.70 mmol/L (150 mg/dL)) or low high-density lipoprotein-cholesterol (HDL-C concentration≤0.91 mmol/L (35 mg/dL)). Biochemical blood examinations were available for 2945 (90.6%) subjects. After adjustment for age, gender, habitation region, body mass index, self reported income, blood glucose concentration, diastolic blood pressure and smoking, dyslipidemia was significantly associated with higher intraocular pressure (P<0.001) and beta zone of parapapillary atrophy (P = 0.03). Dyslipidemia was not significantly associated with the prevalence of glaucoma (P = 0.99), retinal vein occlusions (P = 0.92), diabetic retinopathy (P = 0.49), presence of retinal vascular abnormalities such as focal or general arteriolar narrowing, age-related macular degeneration (P = 0.27), nuclear cataract (P = 0.14), cortical cataract (P = 0.93), and subcapsular cataract (P = 0.67). The results make one conclude that, controlled for systemic and socioeconomic parameters, dyslipidemia was not associated with common ophthalmic disorders including glaucoma and age-related macular degeneration.
Gesehen am 20.02.2019